A Review on Host Genetic Susceptibility to SARS CoV-2 Related Pneumonia - Shubham Dutta; Yatish Ravindra Thakare; Avinash Kshirsagar; Diptendu Sarkar (International Journal of Pharma and Bio Sciences, 2021)
The pandemic of coronavirus started in December 2019 is a great challenge for mankind. Even though the mortality rate is less but still the virus has successively managed to cause this catastrophe. Many theories of the virus emergence have come forward but still the exact origin of the virus is unknown. This disease possesses serious concern as the appearance of the symptoms is different; mild to severe ARDS (Acute respiratory distress syndrome), also the strain circulating in different areas are showing different severity. It is very important to understand the host-pathogen interaction for the complete understanding of the disease. Along with the environmental factors, host genetic factors also play to accomplish disease severity. The main aim of this review is to understand various factors such as host immune response, host genes, age and factors which can change the pathogenesis of the virus from individual to individual. It might be able to address several ways to tackle the virus in different individuals.